A few alternative techniques for the production of olive green shade without the use of the conventional synthetic dyestuffs - Nadkarni, P. S. (Defence Science Journal, 2014)
Investigations were undertaken to explore the possibilities of dyeing cotton fabrics to olive green shade using only mineral pigments or other indigenous and cheap colouring matters. Materials dyed by using such compositions could be used for a variety of purposes, other than Service clothing, such as tentage, canvases, ducks etc. After studying the self shades obtained with various mineral pigments, several compatible combinations were tried out to get the correct olive green shade. It was observed that olive green shade with varying degree of fastness characteristics can be produced by different compositions of mineral pigments with or without synthetic resin bindings. The choice of a specific recipe for dyeing a fabric will however depend upon the end-use of the fabric and the shade fastness characteristics expected of the same.